The megascopic and mesoscopic structure of La Cocha ultramafic body, Sierra Chica of Córdoba, Argentina - Anzil, Patricia Andrea (2009)
The serpentinized ultramafic body of La Cocha is located in the Sierra Chica of Córdoba (31° 36′ 40″ South and 64° 32′ 40″ West). The body is a spinel harzburgite composed of olivine, enstatite and spinel, almost completely hydrated to associations of serpentine minerals. The rock is dark green, foliated, rich in serpentinized olivine and grains or aggregates of enstatite, partially to totally altered to bastite, with spinel as inclusions and a general porphyritic appearance. The S2 metamorphic foliation was determined by a compositional layering defined by the lengthening and concentration of irregular pyroxene layers that alternate with olivine layers. This foliation is affected by S3, composed of serpentine, which is parallel or cut sharply with low angles to S2. The main structure of La Cocha ultramafic body is a low cylindrical recumbent fold interpreted as an "a"-type domal structure which is part of a major sheath fold, currently cut off by erosion. La Cocha ultramafic body is interpreted as an obducted slice of oceanic mantle, probably part of a basal tectonite of an ophiolitic complex. This slice, after its emplacement, was metamorphosed and deformed together with the country rocks. © 2009 Elsevier Ltd. All rights reserved.